Biosynthesis of Nanomaterials by Shewanella Species for Application in Lithium Ion Batteries - Kim, Tae-Yang; Kim, Min Gyu; Lee, Ji-Hoon; Hur, Hor-Gil (Frontiers in Microbiology, 2018)
Nanomaterials exhibit extraordinary properties based on their size, shape, chemical composition, and crystal structure. Owing to their unique properties nanomaterials are preferred over their bulk counterparts for a number of applications. Although conventional physical and chemical routes were established for the massive production of nanomaterials, there are some drawbacks such as environmental burden and high cost that cannot be disregarded. Recently, there has been great interest towards the green synthesis of inorganic nanomaterials. It has been reported that dissimilatory metal reduction by microorganisms is a cost-effective process to remediate toxic organic and inorganic compounds under anaerobic conditions. Particularly, members of the Shewanella genus have been utilized to produce various biogenic nanomaterials with unique micro/nanostructured morphologies through redox transformations as well as to remove harmful metals and metalloids in eco-efficient and environment‐friendly methods under ambient conditions. In the present mini-review, we specifically address the active utilization of microbial respiration processes for the synthesis of novel functional biogenic nanomaterials by the members of the Shewanella genus. This biosynthetic method may provide alternative approaches to produce electrode materials for sustainable energy storage applications.